1991
DOI: 10.1002/jemt.1060170106
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical characteristics of the golgi apparatus

Abstract: Lectinocytochemistry provides a useful tool for localizing subcompartments of the complex reticular apparatus of Golgi. The technique is based on interactions of lectins with glycoconjugates present in the limiting membranes and luminal spaces of Golgi elements. Application of a series of lectins of different sugar specificities permits a differentiation between Golgi subcompartments containing glycoconjugates with different oligosaccharide side chains. These may be a) differnet glycoconjugates or b) glycoconj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
6
6
0
Order By: Relevance
“…In fact, the linkage a-GalNAc residues are known, in most instances, to be attached by (3-Ga1 and/or p-GlcNAc, and then oligosaccharide backbones composed of the repetition of (3-Gal and (3-GlcNAc residues are elongated (10,11,21,22,28). In the present study, the s u m , KATAOKA SBA label reappeared in trans-most cisternae and continued to mucous granules, and this result agrees with previous studies which showed that oligosaccharide backbones are often terminated with a-GalNAc (7,10,11,19,22,29). This implies that the terminal a-GalNAc residues are transferred to oligosaccharide backbones in the trans-most Golgi cisternae.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, the linkage a-GalNAc residues are known, in most instances, to be attached by (3-Ga1 and/or p-GlcNAc, and then oligosaccharide backbones composed of the repetition of (3-Gal and (3-GlcNAc residues are elongated (10,11,21,22,28). In the present study, the s u m , KATAOKA SBA label reappeared in trans-most cisternae and continued to mucous granules, and this result agrees with previous studies which showed that oligosaccharide backbones are often terminated with a-GalNAc (7,10,11,19,22,29). This implies that the terminal a-GalNAc residues are transferred to oligosaccharide backbones in the trans-most Golgi cisternae.…”
Section: Discussionsupporting
confidence: 93%
“…Labeling with SBA first appeared in cis-Golgi cisternae, implying the transfer of the linkage a-GaWac of 0-linked oligosaccharides. This observation further indicates that the subcellular domain where the initial 0-glycosylation takes place is the cis-Golgi cisternae but not the rough endoplasmic reticulum, which agrees with previous biochemical and cytochemical observations (7,8,19,27). SBA binding disappeared in intermediate cistemae.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It seems that the internalized plasma membrane constituents (including receptors and ligands) are delivered to the Golgi apparatus (Gonatas et al, 1975;Herzog & Farquhar, 1977;Roth, 1978;Joseph et al, 1979;Thyberg, 1980;Thyberg et al, 1980). A recent study showed that different glycoconjugates either newly synthesized or recycling could be differentiated in the Golgi subcompartments (Pavelka & Ellinger, 1991); these authors demonstrated that the binding sites for Gal-affinity lectins were localized predominantly in the transmost Golgi cisterna. It is therefore significant that the Golgi apparatus in the 'intermediate' ramified cells (cells with long thick processes and cells with thin processes) was stained with GSA I-B4 lectin especially at its trans saccules and trans tubular network.…”
Section: Internalization and Synthesis And/or Modification Of Galactomentioning
confidence: 98%
“…Combined electron microscopic and cytochemical techniques have made it possible to divide the stacks into three major subcompartments-cis, medial, and trans-with distinct differences in composition and function (Farquhar and Palade, 1981;Pavelka and Ellinger, 1991;Roth, 1991;Slot and Geuze, 1983). The Golgi stacks are frequently located in a circumscribed region close to the nucleus and display a close relationship to microtubules radiating from organizing centers associated with the centrosome.…”
Section: Morphology Of Interphase Cellsmentioning
confidence: 99%